Slow and Steady Wins the Race: A Solid Case for a 3-Stage Approach in Ulcerative Colitis. Issue 12 (December 2021) - Plietz, Michael C.; Kayal, Maia; Rizvi, Anam; Bangla, Venu G.; Khetan, Prerna; LaChapelle, Christopher R.; Whitney, Stewart L.; Huber, Hans M.; Hwa Walter Wang, Yun; Radcliffe, Marlana; Khaitov, Sergey; Sylla, Patricia A.; et al.
Abstract : BACKGROUND: Approximately 10% to 20% of patients with ulcerative colitis require surgery during their disease course, of which the most common is the staged restorative proctocolectomy with IPAA. OBJECTIVE: The aim was to compare the rates of anastomotic leaks among all staged restorative proctocolectomy with IPAA procedures. DESIGN: This was a retrospective cohort study. SETTINGS: This study was conducted at a single tertiary care IBD center. PATIENTS: All patients with ulcerative colitis or IBD-unspecified who underwent a primary total proctocolectomy with IPAA for medically refractory disease or dysplasia between 2008 and 2017 were identified. MAIN OUTCOME MEASURES: The primary outcome was anastomotic leak within a 6-month postoperative period. Univariate and multivariate logistic regression were used to compare patients with and without anastomotic leaks. RESULTS: The sample was composed of 584 nonemergent patients, of whom 50 (8.6%) underwent 1-stage, 162 (27.7%) underwent 2-stage, 58 (9.9%) underwent modified 2-stage, and 314 (53.7%) underwent a 3-stage total proctocolectomy with IPAA. The primary indication was medically refractory disease in 488 patients and dysplasia/cancer in 101 patients. Anastomotic leak occurred in 10 patients (3.2%) after 3-stage, 14 patients (8.6%) after 2-stage, 6 patients (10.3%) after modified 2-stage, and 10 patients (20.0%) after a 1-stage procedure. A 3-stage procedure had fewer leaks and additional procedures for leaks compared with 1- and modified 2-stage procedures ( p < 0.03). The 3-stage procedure had fewer combined anastomotic leaks and pelvic abscesses than all of the other staged procedures ( p < 0.05). LIMITATIONS: This study was limited by its retrospective design and evolving electronic medical charts system. CONCLUSIONS: The 3-stage total proctocolectomy with IPAA is the optimal staged method in ulcerative colitis to reduce leaks and related complications. See Video Abstract at http://links.lww.com/DCR/B693 . LENTO Y CONSTANTE GANA LA CARRERA: UN CASO SÓLIDO PARA UN ENFOQUE DE TRES ETAPAS EN LA COLITIS ULCEROSA: ANTECEDENTES: Aproximadamente el 10-20% de los pacientes con colitis ulcerosa requieren cirugía durante el curso de su enfermedad, de los cuales la más común es la proctocolectomía restauradora escalonada con anastomosis con bolsa ileo-anal. OBJETIVO: El objetivo fue comparar las tasas de fugas anastomóticas entre todos los procedimientos de proctocolectomía restauradora por etapas con procedimiento de anastomosis con bolsa ileo-anal. DISEÑO: Este fue un estudio de cohorte retrospectivo. ENTORNO CLÍNICO: Este estudio se llevó a cabo en un único centro de atención terciaria de tercer nivel para enfermedades inflamatorias del intestino. PACIENTES: Se identificaron todos los pacientes con colitis ulcerosa o enfermedad inflamatoria intestinal inespecífica que se sometieron a una proctocolectomía total primaria mas anastomosis con bolsa ileo-anal por enfermedad médicamente refractaria o displasia entre 2008 y 2017. PRINCIPALES MEDIDAS DE RESULTADO: El resultado primario fue la fuga anastomótica dentro de un período posoperatorio de seis meses. Se utilizó regresión logística univariante y multivariante para comparar pacientes con y sin fugas anastomóticas. RESULTADOS: La muestra estuvo compuesta por 584 pacientes no emergentes, de los cuales 50 (8, 6%) se sometieron a una etapa, 162 (27, 7%) se sometieron a dos etapas, 58 (9, 9%) se sometieron a modificación en dos etapas y 314 (53, 7%) se sometieron a una proctocolectomía total en tres tiempos mas anastomosis con bolsa ileo-anal. La indicación principal fue enfermedad médicamente refractaria en 488 pacientes y displasia / cáncer en 101 pacientes. Se produjo una fuga anastomótica en 10 (3, 2%) pacientes después de tres etapas, 14 (8, 6%) pacientes después de dos etapas, 6 (10, 3%) pacientes después de dos etapas modificadas y 10 (20, 0%) pacientes después de una etapa procedimiento. Un procedimiento de tres etapas tuvo menos fugas y procedimientos adicionales para las fugas en comparación con los procedimientos de una y dos etapas modificadas ( p <0.03). El procedimiento de tres etapas tuvo menos fugas anastomóticas y abscesos pélvicos combinados que todos los demás procedimientos por etapas ( p <0, 05). LIMITACIONES: Este estudio estuvo limitado por su diseño retrospectivo y su sistema de registros médicos electrónicos en evolución. CONCLUSIONES: La proctocolectomía total en tres etapas mas anastomosis con bolsa ileo-anal es el método óptimo por etapas en la colitis ulcerosa para reducir las fugas y las complicaciones relacionadas. Consulte Video Resumen en http://links.lww.com/DCR/B693 .